Customs Officers under Martial Law in Ukraine: Constitutional and Administrative Dimensions - Cherkunov, Oleksandr (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2025)
This article explores the legal status and functional transformations of customs officers in Ukraine during the period of martial law. It examines the constitutional framework of emergency governance, the administrative specifics of public service under crisis, and the practical implications of accelerated legal procedures and ad hoc appointments in the customs system. Drawing on comparative constitutional insights and doctrinal commentary, the study highlights structural deviations from standard service models and the legal uncertainty surrounding the rights and responsibilities of customs personnel in wartime. The article argues for a clearer statutory delineation of the emergency public service regime to enhance legal predictability, institutional accountability, and resilience. The findings are based on legal analysis and doctrinal sources from Ukraine, Poland, France, Germany, and the UK.